MODELING AND ANALYSIS OF DROP SIZE IN A MODIFIED SPRAY COLUMN FOR AROMATICS EXTRACTION - Marwa Al-Shammary; Raghad F. Almilly (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Aromatic compounds are considered the building block for petrochemical industries. In this study, a new pilot-scale counter-current modified spray column was designed and constructed for extracting aromatic compounds from reformate-heavy naphtha (RHN) using furfural as solvent. RHN and furfural were provided by Al-Dora Refinery in Iraq. The new design included a rotor added to the conventional spray column. The effects of solvent-feed ratio (S/F) (0.25-2) and rotor speed (0-1000 rpm) were studied. The extraction efficiency and Sauter mean diameter (d32) were investigated experimentally and modeled by dimensional analysis. The experimental results showed that the extraction efficiency varied significantly with rotor speed and S/F ratio recording 96.5% without plate, and 92.5% with plate at 0 rpm rotor speed. The experimental results also showed that d32 values ranged from 0.0025 m to 0.0055 m, corresponding with changes in efficiency. Depending on the experimental results, a correlation was derived for the efficiency and d32 based on the effective dimensionless numbers in the system. The modeling results demonstrated that Reynolds (Re) and Weber We numbers were the most effective dimensionless groups that affected the extraction efficiency and d32 values.